Mental Maps of the World: The Case of Singapore Students - Kong, Lily (Institutional Knowledge at Singapore Management University, 1994)
Using mental maps as the basis of discussion, this paper attempts to explore how Singapore students view the world, and conversely, how students from the rest of the world view Singapore, using data collected between 1985 to 1987 from 3,863 university students in 52 countries. The results reveal the factors that influence students' perceptions. The paper argues that progress beyond purely parochial views of the world is imperative if world understanding, and eventually world peace, is to be attained.